IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM PENDIDIKAN KARAKTER DI SD NEGERI 1 TAMBAKREJO: penelitian kualitatif - Annisa Laili Rahmadani; Soegeng Ysh; Wijayanti, Arfilia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The background that drives this research is that the implementation of SBM at SD N 1 Tambakrejo looks good and effective, has school quality and adequate facilities and infrastructure. Even though the MBS at this school is considered good, several students have less than desirable characteristics in school and outside school activities. Due to the students' poor character, SD Negeri 1 Tambakrejo implemented SBM in character education. The problem in this research is